MENGEMBANGKAN SIKAP PROAKTIF TERHADAP TUNTUTAN PERUBAHAN - Purwatiningtyas, Purwatiningtyas (Fokus Ekonomi, 2006)
Change, although externally may appear to be about changing jobs, places, products, etc. actually occurs first inside people's heads. And there's the rub. When organizations try to change without understanding this invisible element, any change is doomed to serious problems and failure. Then the organizations must be proactive the challenge environment. There are three position at the change organization : proactive aptitude, must live entrepreneurship and continuous learning at change organization.Keywords : Change, Proactive Aptitude And  Organization Change